The Response of Adding Nanocarbon to the Combustion Characteristic of Crude Coconut Oil (CCO) Droplets - Ena Marlina; Mochammad Basjir; Rully Dyah Purwati (Automotive Experiences, 2022)
One of the strong candidates for biodiesel is Crude Coconut Oil (CCO) but its high viscosity cannot be applied directly without treatment. Therefore, nanocarbon is added to reduce the viscosity of CCO. Nanocarbon is a natural material with semiconductor properties, a good heat conductor, and can attract other molecules. By adding nanocarbon, it is expected to reduce the viscosity of CCO. This study aimed to determine the combustion characteristics of droplets on CCO by adding nanocarbon by 1% and 5%. The method used was a true experiment with droplets, which dripped on the thermocouple with activation energy from the heater. The results showed that CCO burned 0.933s with a droplet diameter of 4.307mm, droplet diameter of 5.472 mm. By adding 5% nanocarbon to CCO, the CCO burned faster, more reactive, and the ignition was shorter than the pure CCO and 1% CCO.